Neuronal correlates of endogenous selective attention in the endbrain of crows - Lukas Alexander Hahn; Erica Fongaro; Jonas Rose (Communications Biology)
Abstract The ability to direct attention and select important information is a cornerstone of adaptive behavior. Directed attention supports adaptive cognitive operations underlying flexible behavior, for example in extinction learning, and was demonstrated behaviorally in both mammals and in birds. The neural foundation of such endogenous attention, however, has been thoroughly investigated only in mammals and is still poorly understood in birds. And despite the similarities at the behavioral level, cognition of birds and mammals evolved in parallel for over 300 million years, resulting in different architectures of the endbrain, most notably the absence of cortical layering in birds. We recorded neuronal signals from the nidopallium caudolaterale, the avian equivalent to mammalian pre-frontal cortex, while crows employed endogenous attention to perform change detection in a working memory task. The neuronal activity profile clearly reflected attentional enhancement of information maintained by working memory. Our results show that top-down endogenous attention is possible without the layered configuration of the mammalian cortex.